Thrombotic microangiopathy following gene therapy for 5q-spinal muscular atrophy - Gontijo Camelo, Clara; Mendonça, Rodrigo Holanda; Moreno, Cristiane Araújo Martins; Ferreira, Juliana Caires Oliveira Achili; Ortega, Adriana Banzzatto; van der Linden, Vanessa; Campos, Rejane Souza Macedo; van der Linden, Helio; da Cunha, Natalia Spinola Costa; Gurgel-Giannetti, Juliana; Chaves, Janaina Monteiro; Miranda, Silvana Maria Carvalho; et al. (Gene therapy, 2025)
Onasemnogene abeparvovec (OA) is the first gene replacement therapy (GT) approved for 5q spinal muscular atrophy (SMA). While effective, it can cause severe side effects, including thrombotic microangiopathy (TMA). The pathophysiology, risk factors, and management of viral-vector-related TMA remain unclear. This study aimed to evaluate TMA frequency among Brazilian patients treated with OA and characterize their clinical and laboratory profiles. This retrospective, multicenter study analyzed 294 Brazilian patients with 5q SMA treated with OA between October 2020 and September 2024, of whom seven (2.4%) developed TMA. The average age at OA administration was 20.4 months, and the average weight was 11.5 kg. Three patients had documented infections before OA administration. TMA symptoms appeared within 6-10 days post-infusion. All patients showed hemolytic anemia, thrombocytopenia, and at least one organ dysfunction. Treatment included plasmapheresis in two cases and increased corticosteroid doses in four cases. One patient died from TMA complications. Whole exome sequencing in five patients identified no pathogenic variants linked to TMA. TMA is a rare but severe complication of OA therapy for SMA. Prompt recognition and management, often with corticosteroids, are crucial for improving outcomes.